Gravity Model dalam Place-Making Pola Interaksi Spasial di Pulau Kalimantan - Ahmad Aguswin; Akhmad Akromusyuhada (DPPM Universitas Pelita Bangsa, 2020)
One of the challenges faced in the development of a city comes from population problems. This is related to the increasing number of population each year which is relatively high and the population distribution is not evenly distributed. The island of Kalimantan has special characteristics in terms of culture of migrants as well as in dealing with population problems, especially due to the phenomenon of migration. Population movement causes uneven distribution of the population and affects population growth in an area and has an impact on regional development. As a result, the population is only concentrated at a certain point in the region or in areas of high attractiveness. On the island of Kalimantan, there are several regions that are administratively and demographically attractive compared to other areas in the vicinity, such as Kota Samarinda, Balikpapan, and Bontang in East Kalimantan Province and Kota Banjarmasin in South Kalimantan Province. Spatial interaction analysis can estimate the attractiveness of a location compared to other locations in its vicinity, so that it can be seen that the pattern of population movements that tend to lead to areas of higher attractiveness. The results of an empirical study using a gravity model indicate that the population factor in the origin and destination areas and distance affects migration on the island of Kalimantan. The results of the study indicate that distance has a negative effect on migration, while the population of origin and destination areas has a positive effect on migration. In addition, job opportunities, facilities in the city, and accessibility also affect migration. Overall, the areas with the highest attractiveness used population variables and were the main destinations for residents to move to Kota Samarinda, Balikpapan, and Bontang in East Kalimantan Province as well as Kota Banjarmasin in South Kalimantan Province. Using the job opportunity variable also shows the same pattern using the population number variable, where the main purpose of residents to move is in these 4 cities.